Taxonomic novelties in Neotropical Chrysobalanaceae: towards a monophyletic Couepia - Sothers, Cynthia; Prance, Ghillean; Buerki, Sven; de Kok, Rogier; Chase, Mark (Phytotaxa, 2014)
Recent molecular phylogenetic studies in Chrysobalanaceae as well as new analyses presented in this study cast doubt on the monophyly of the three largest genera in the family, Couepia, Hirtella and Licania. Couepia, a Neotropical genus, had species appearing in four separate clades, the majority of species sequenced, however, form a highly supported clade, referred to here as core Couepia (including the type species). These results lend support to a revised taxonomy of the genus, and to resolve Couepia as monophyletic the following taxonomic changes are here proposed: Couepia recurva should be transferred to Hirtella, C. platycalyx transferred to Licania, C. longipendula and C. dolichopoda transferred to Acioa, and a new genus, Gaulettia, is proposed to accommodate species of the Gaulettia clade and allies.